2010
DOI: 10.1016/j.jsb.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Laminin chain assembly is regulated by specific coiled-coil interactions

Abstract: Laminins are large heterotrimeric, multidomain proteins that play a central role in organising and establishing all basement membranes. Despite a total of 45 potential heterotrimeric chain combinations formed through the coiled-coil domain of the 11 identified laminin chains (α1–5, β1–3, γ1–3), to date only 15 different laminin isoforms have been reported. This observation raises the question whether laminin assembly is regulated by differential gene expression or specific chain recognition. To address this is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 26 publications
(27 reference statements)
0
34
0
1
Order By: Relevance
“…The α, β, and γ subunits can be arranged either clockwise or counter clockwise when viewed down the coiled-coil axis. The order of subunits in the trimer underlies the mechanism of combinatorial assembly of laminin isotypes (35) and therefore is key to understanding the complexity and diversification of the laminin family. We reasoned that the alternative subunit arrangements could be distinguished without knowledge of the register of the three strands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The α, β, and γ subunits can be arranged either clockwise or counter clockwise when viewed down the coiled-coil axis. The order of subunits in the trimer underlies the mechanism of combinatorial assembly of laminin isotypes (35) and therefore is key to understanding the complexity and diversification of the laminin family. We reasoned that the alternative subunit arrangements could be distinguished without knowledge of the register of the three strands.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that N1750 is substituted by glycine in laminin β3 chains. It has been observed that β3 forms heterodimeric assembly intermediates with γ2 but not with the γ1 or γ3 paralogs (35). The γ2 subunit differs from γ1 and γ3 at the residue immediately following the conserved Q1566, possessing an arginine instead of a glutamate.…”
Section: Resultsmentioning
confidence: 99%
“…Charged residues within the heptad repeats of the coiled-coil restrict the number of allowed heterotrimers (Beck et al 1993;Macdonald et al 2010) to generate the following (confirmed) vertebrate heterotrimers: laminins-111 (i.e. a1b1g1), 121, 211, 213, 221, 311, 312, 321, 332, 411, 421, 422, 423, 511, 521, and 523 (Aumailley et al 2005;Macdonald et al 2010). The a3A subunit, which lacks the amino-terminal domains of the short arm, also exists as a longer (a3B) splice-variant with a full short arm.…”
Section: Laminin Familymentioning
confidence: 99%
“…Five α, three β and three γ chains have been identified forming 16 different heterotrimers (Aumailley et al, 2005;Macdonald et al, 2010) with overlapping yet distinct tissue distribution and function (Colognato and Yurchenco, 2000;Durbeej, 2010). The current nomenclature for laminins consists of three numbers, denoting the its chain composition, e.g.…”
Section: Introductionmentioning
confidence: 99%